2015
DOI: 10.1007/jhep01(2015)010
|View full text |Cite
|
Sign up to set email alerts
|

Physical states in the canonical tensor model from the perspective of random tensor networks

Abstract: Tensor models, generalization of matrix models, are studied aiming for quantum gravity in dimensions larger than two. Among them, the canonical tensor model is formulated as a totally constrained system with first-class constraints, the algebra of which resembles the Dirac algebra of general relativity. When quantized, the physical states are defined to be vanished by the quantized constraints. In explicit representations, the constraint equations are a set of partial differential equations for the physical wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(76 citation statements)
references
References 85 publications
(189 reference statements)
2
71
0
Order By: Relevance
“…• The expectation values of some observables are computed by the numerical simulations, and it is observed that there exists a transition region around R ∼ N 2 /2. Intriguingly, the location is in good coincidence with R = (N + 2)(N + 3)/2 that is required by the consistency of the tensor model (the hermiticity of its Hamiltonian constraint) [18,15,29]. Presently, this coincidence is mysterious, since there are no apparent connections between the transition and the consistency.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…• The expectation values of some observables are computed by the numerical simulations, and it is observed that there exists a transition region around R ∼ N 2 /2. Intriguingly, the location is in good coincidence with R = (N + 2)(N + 3)/2 that is required by the consistency of the tensor model (the hermiticity of its Hamiltonian constraint) [18,15,29]. Presently, this coincidence is mysterious, since there are no apparent connections between the transition and the consistency.…”
Section: Introductionmentioning
confidence: 83%
“…where we have determined the overall factor by requiring f (2) N,R,Λ ij (0) = 1, the product is over all the eigenvalues of the matrix Λ ij , and h N,R (x) is defined in (15).…”
Section: Now Let Us Apply the Wick Contractions To What Is Obtained Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In [25], it was argued and explicitly shown for some simple cases that the wave function (76) has coherent peaks for some specific loci of P abc where P abc is invariant under Lie-group transformations (namely, P abc = h a a h b b h c c P a b c for ∀ h ∈ H with a Lie-group representation H). In fact, a tensor model [20,21,22] in the Hamilton formalism [23,24] has a similar wave functionψ(P ) R with a power R andψ(P ) very similar to ψ(P ) [18], and it was shown in [19] that the wave function of this tensor model has similar coherent peaks. To consistently interpret this phenomenon as the preference for Lie-group symmetric configurations in the tensor model, we first have to show that we can apply the quantum mechanical probabilistic interpretation to the wave function, namely, the wave function must be absolute square integrable.…”
Section: Application To a Tensor Modelmentioning
confidence: 99%
“…One of our motivations to initiate the study of the model (1) is to investigate the properties of the wave function [18,19] of a tensor model [20,21,22] in the Hamilton formalism [23,24], which is studied in a quantum gravity context. The expression (1) can be obtained after integrating over the tensor argument of the wave function of the toy model introduced in [25], which is closely related to this tensor model.…”
Section: Introductionmentioning
confidence: 99%